Impact of Eucalyptus plantations on ecosystem services in the Upper Blue Nile basin of Ethiopia - Abdurohman Yimam; Asnake Mekuriaw; Dessie Assefa; Woldeamlak Bewket (Environmental and Sustainability Indicators, 2024)
In the Northern highlands of Ethiopia, Eucalyptus plantations have been widely established since the 1970s. However, there have been debates and concerns about the impact of these plantations on ecosystem services. Therefore, the study aimed to assess the impact of monoculture Eucalyptus plantations on ecosystem service values (ESVs) in the upper Blue Nile part of Ethiopia. We used Landsat satellite images (captured in 1993, 2004, 2014, and 2023) for land use/cover assessment. The images were classified using the Random Forest (RF) algorithm in the R open-source software. For ecosystem services valuation, we used the benefit transfer method, which allowed us to estimate ESVs by applying both global and local value transfer coefficients. The results show a significant expansion of Eucalyptus plantations, with the highest net change (180%) between 1991 and 2023. The estimated global ESVs ranged from US$206 million in 1991 to US$208 million in 2023, with croplands contributing the largest share (75%). However, specific ESVs related to nutrient cycling, habitat refuge, pollination, and culture declined due to decreasing ESVs of forest land, shrub land, and grazing land over the study period (1991–2023). In addition, ESVs associated with food production declined in the latter period (2014–2023) due to the conversion of croplands into Eucalyptus plantations and shrub lands. This study highlights the need for informed decision-making in land use systems, considering the trade-off between increasing productivity and the loss of other ecosystem functions and services.